Evaluación de la eficiencia energética en la implementación de un sistema de iluminación en la Carrera de Agroindustria de la ESPAM-MFL. - Aguayo Zambrano, Dayana Elizabeth (2018)
The present investigation had as objective the implementation of a system of illumination, conformed by four luminaires: Incandescent, fluorescent, LED warm light and LED light day; the system was implemented in the Agroindustry carier at Escuela Superior Politécnica Agropecuaria de Manabí ¨Manuel Félix López¨. Energy efficiency is considered as an alternative that allows analyzing and dealing with problems of increasing energy consumption. The International Energy Agency (IEA) considers that energy savings and efficiency must contribute 43% of the reduction of CO2 emissions to the atmosphere. The energy efficiency was determined through the following parameters: energy consumption, luminosity and temperature of each luminaire. Obtaining as a result, according to the tests carried out on the implemented system, the luminaires with warm light LED spotlights showed to be more appropriate for outdoor lighting because they presented a lower energy consumption of 5.4 kWh, emitting 4.320 g of CO2, to their lesser amount of temperature and an average luminous efficiency of 108.6 lx, 182.6 lx and182 lx. The design of the lighting system was carried out with the collaboration of the personnel in charge of the Planning Department of the institution.